Highlights from IFPRI's West and Central Africa Office - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
IFPRI established the West and Central Africa office (WCAO) in 2010 to better meet local research and capacity needs for Reducing poverty and ending malnutrition in the region. Although the West and Central Africa region has experienced strong economic growth over the past 15 years, it faces challenges from increasing urbanization, a growing middle class, transforming agrifood systems, and the intensifying effects of climate change. WCAO is helping to address these pressing problems. It also supports the implementation of the Comprehensive Africa Agriculture Development Programme (CAADP) and works with regional bodies such as the Economic Community of West African States (ECOWAS) and individual countries to provide evidence-based agricultural policy solutions and capacity-strengthening support. WCAO hosts staff from two IFPRI research divisions: the Markets, Trade, and Institutions Division (MTID) and the Poverty, Health, and Nutrition Division (PHND).